An Optimized Method to Assess Viable Escherichia coli O157:H7 in Agricultural Soil Using Combined Propidium Monoazide Staining and Quantitative PCR - Fu, Yulong; Ye, Zhe; Jia, Yangyang; Fan, Jiahui; Hashmi, Muhammad Zaffar; Shen, Chaofeng (Frontiers in Microbiology, 2020)
Agricultural soil contaminated by manure is becoming an important source for the transmission of foodborne pathogens. There is an urgent need for a rapid and accurate method for viable pathogen detection in the agricultural soils samples. Propidium monoazide (PMA) is a DNA-binding dye that can inhibit the amplification of DNA from dead cells through subsequent quantitative polymerase chain reaction (qPCR), thus allowing for viable cells detection and quantification. The objective of this study was to detect viable Escherichia coli O157:H7 in the agricultural soils by PMA-qPCR. In this study, cell extraction and gradient density centrifugation were incorporated before PMA-qPCR to reduce the interference of soil particle including turbidity and a high ratio of dead cells. The optimized treatment conditions were determined as follows, the maximum removal of DNA from dead cells was achieved by 1.067 g/mL Percoll of centrifugation and 50 μM PMA treatment. Under these conditions, the turbidity of paddy soil suspensions decreased from 3500 to 28.4 NTU, and the ratio of viable cells to dead cells increased from 0.001 % to 1.025 %. For typical agricultural soils collected in China, as low as 102 CFU/g of viable cells could be accurately detected in the presence of a large number of dead cells (107 CFU/g) by the optimized PMA-qPCR. Significantly, with comparable accuracy, the optimized PMA-qPCR assay was more sensitive, accessible and rapid than conventional culture methods. In addition, the viable but non-culturable (VBNC) state of E. coli O157:H7 cells in paddy soils, which often escaped the detection by conventional culture methods, could be quantitatively characterized by the optimized PMA-qPCR method. Potentially, the optimized PMA-qPCR can be further applied for viable pathogens detection and give insight into the prevalence of VBNC E. coli O157:H7 in agricultural soil.